Climate and groundwater effects on the establishment, growth and death of Prosopis caldenia trees in the Pampas (Argentina) - Bogino, Stella Marys (2011)
Semiarid woodlands dominated by Prosopis caldenia thrive at the dry edge of the Argentinean Pampas. Deforestation and increased precipitation have driven sustained water table level rise in the region that are likely to affect the dynamics of remnant woody vegetation patches. Here we analyze the effect of climate and groundwater level on the establishment, growth and death of P. caldenia located on lowland (current water table < 0.5 m deep) and upland (current water table 8 m deep) positions within rolling sandy landscape. Standard dendrochronological techniques were applied on 98 cross sections and cores of P. caldenia trees. Results allowed us to estimated that trees in the lowland established a few years earlier than in the upland (1929 vs. 1936) and died between 1991-2002, while trees in higher positions are still alive. As a result of a faster growth in the lowland, maximum mean radial growth took place earlier (1960s vs. 1990s). While mean annual chronologies were not associated across stands, an opposite highly significant association was found for the mean growth trends suggesting long-term effects of water table depths on growth. We found a contrasting different association between mean annual growth and climate, with lowland trees showing a negative response to precipitation before and during the growing season, and upland trees displaying a positive response to summer rainfall inputs. Temperature at the end of the growing season had a positive effect in the lowland whereas temperature during the growing season had a positive effect in the upland. These results show how groundwater can induce diverging sensitivity of forest growth and survival to climate variability, enhancing growth at optimum depths (2-8 m in our study) but depressing it or even killing trees when it approaches the surface (< 2 m in our study). Groundwater dynamic should be considered in forest management and conservation strategies in semiarid woodlands in Central Argentina.